Short-Term Prediction Of Covid-19 Cases Using Ensemble Regression Models In Tamilnadu Districts - et. al., V.Ashridurga , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Regression based outfit learning model that requires the previous 14 days information into record to anticipate COVID-19 cases for the time being. Accurately expect the fundamental infection similarly as effectively directing meager resources. It is valuable to plan medical clinics and medical services laborers with legitimate gear like beds, ventilators and so forth ahead of time with no troubles. To this end, this structure designs a backslide based gathering learning model containing Linear backslide, Ridge, LASSO, ARIMA, and SVR that requires the previous 14 days data into record to anticipate the amount of new Corona cases briefly (Future three days). The social affair model yields the best show by thinking about the introduction of the large number of models. This framework thinks about information from Tamilnadu Districts. The outcomes regarding relative rate mistake show that the group strategy gives predominant forecast.